Explaining Workplace Spirituality in a Government Agency: The Interactive Effect of Turnover Intention, Employee Performance, and A Multi-Group - Siswanto,; Falabiba, Nilna Elmawati (International Journal of Psychosocial Rehabilitation, 2020)
Agricultural Technology Assessment Center (BPTP) is a government agency aimed at achieving success in the global era. Therefore, this organization uses bureaucratic reforms, which requires government agencies to improve employee performance to enhance its operations. This study, therefore, aims to analyze the influence of workplace spirituality on turnover intention and employee performance. It also examines the role of gender in multi-groups using the quantitative method. Data were randomly obtained from a total of BPTP employees in East Java, with SEM PLS used to determine the gender variables in multi-group analysis. The results showed that workplace spirituality has a positive effect on employee performance and a negative influence on turnover intention. The findings also show a different role from moderating variables, namely gender clusters in multi-group analysis.